PENGARUH AL-SYATIBI TERHADAP EKONOMI ISLAM KONTEMPORER - Nabila Keysha Mutmainah; Cynthia Ananda Br Tarigan; Nurul Hidayah; Fahrinsal Sitorus; Fitri Hayati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the relevance of Imam Abu Ishaq al-Syatibi's thoughts on Maqasid al-Syari'ah in the development of contemporary Islamic economics. Al-Syatibi divides Maqasid al-Syari'ah into three levels: dharuriyyat (basic needs), hajiyyat (additional needs), and tahsiniyyat (complementary needs), which encompass the five fundamental elements of human life: religion, life, intellect, lineage, and wealth. This study employs a qualitative approach using literature review methods to explore the influence of al-Syatibi's thought on economic policies, Islamic financial products, and the formulation of socially just policies. The research findings indicate that the application of Maqasid al-Syari'ah principles can enhance the well-being of the community through fair wealth distribution, productive zakat management, and the development of the Islamic financial sector. Al-Syatibi's thought is also relevant in formulating fiscal policies focused on social justice and poverty alleviation, as well as in addressing global economic challenges such as social inequality and environmental degradation.